International Standards to Criminalizing of Terrorism and The Range of The National Legislature’s Commitment to Them: A Comparative Analytical Study - Omed Safary Hasan; Majeed Khedher Ahmad (QALAAI ZANIST SCIENTIFIC JOURNAL, 2022)
There are several international standards in the agreements, decisions and recommendations regarding criminalizing terrorist acts, and some of these agreements, decisions and recommendations require States to stipulate these standards in their internal penal legislations, and also require States to cooperate with each other to combat terrorism. Paying attention to making agreements to formulate standards criminalizing terrorism at the international level goes back to the second half of the last century, and attempts have been increased to issue United Nations Security Council resolutions and recommendations of the Financial Action Task Force after the events of (11/September). Agreements, resolutions and recommendations do not require States to stipulate such standards or texts, in the same way as they are stipulated in the conventions, in the internal legislations, but there is a kind of flexibility and leniency in abiding by international standards for criminalizing and combating terrorism. The Iraqi and Kurdistan legislators are highly committed to these international standards to criminalize terrorism acts in the Iraqi constitution of 2005, as well as in other legislations specific to combating terrorism and other legislations related to criminalizing and combating terrorism. There are some international institutions in charge of monitoring the activities of countries in criminalizing terrorism and these institutions provide recommendations and instructions on how to criminalize terrorism, such as the United Nations Counter-Terrorism Committee, the Financial Action Task Force Committee and the United Nations Office on Drugs and Crime. In case of non- commitment by countries to the standards of criminalization and combating terrorism, there are economic sanctions imposed on countries, especially by the Financial Action Task Force.